Functional Ovarian Cysts in Artificial Frozen-Thawed Embryo Transfer Cycles With Depot Gonadotropin-Releasing Hormone Agonist - Ji, Hui; Su, Yan; Zhang, Mianqiu; Li, Xin; Li, Xiuling; Ding, Hui; Dong, Li; Cao, Shanren; Zhao, Chun; Zhang, Junqiang; Shen, Rong; Ling, Xiufeng (Frontiers in Endocrinology, 2022)
Objectives To investigate the incidence of functional ovarian cysts, its influence on clinical rates, and proper management after depot gonadotropin-releasing hormone (GnRH) agonist pretreatment in artificial frozen-thawed embryo transfer cycles (AC-FET). Methods This retrospective cohort study involved 3375 AC-FET cycles with follicular-phase depot GnRH agonist administration between January 2017 and December 2020. Subjects were divided into a study group (cycles with cyst formation) and a control group (cycles without cyst formation). The study group was matched by propensity scoring matching with the control group at a ratio of 1:2. For patients with ovarian cyst formation, two major managements were used: a conservative approach (i.e., expectant treatment) and a drug approach (i.e., continued agonist administration). The primary outcome was live birth rate (LBR). Results The incidence of functional ovarian cysts following pituitary downregulation is 10.1% (341/3375). The study group exhibited a LBR similar to the control group (54.5% vs. 50.1%, adjusted odds ratio [aOR] 1.17, 95% confidence interval [CI] 0.88–1.56, P = 0.274). Patients with a lower body mass index and anti-Müllerian hormone, and a higher basal estradiol level were more susceptible to developing functional ovarian cysts. The LBR decreased after the drug approach compared with the conservative approach, but not significantly (aOR 0.63, 95% CI 0.35–1.14, P = 0.125). Following the conservative approach, cycles arrived at live births had a significantly shorter duration from the detection of functional cysts to the start of endometrium preparation (15.7 ± 5.1 days vs. 17.4 ± 5.3 days, P = 0.009) and a significantly higher proportion of ovarian cysts on the initial day of exogenous hormone supplementation (51.4% vs. 30.3%, P = 0.001). After controlling for all confounders, the differences remained statistically significant. Conclusions It is unnecessary to cancel cycles that experience functional ovarian cyst formation. Conservative management and further agonist suppression protocol had similar pregnancy rates. However, a conservative approach was recommended due to its lower cost and fewer side effects. Our findings support a shorter waiting period when choosing the conservative protocol.